Strategi Perencanaan Pembangunan Dalam Meningkatkan Kapasitas Perekonomian Kota Medan Provinsi Sumatera Utara - Fitrah Ilham Ramdhan; Muhammad Zaky Abdullah Hutauruk; Achmad Alhafiz lubis; Nurhayati Harahap (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
This research aims to look at development planning strategies in increasing economic capacity in the city of Medan, which is the third largest city after Jakarta and Surabaya, and has received the title as a metropolitan city. Medan city has an area of ​​265.10 km2 and has a population of around 2,478 ,145 people (2017). Currently it is a city that is continuously developing. The main objective of this research is to analyze the role of development planning strategies in strengthening the city's economic sector. The research methods used include primary data collection through interviews and surveys, as well as secondary data analysis from trusted sources. This study will identify factors that influence the economic capacity of Medan City, including infrastructure, economic policies, human resources, and main economic sectors. In addition, this research will evaluate various development planning strategies that can be implemented to increase the city's economic competitiveness, including infrastructure development, increasing market access, industrial development, and increasing workforce skills. It is hoped that the research results will provide a deeper understanding of how development planning strategies can be the key to optimizing the economic potential of Medan City. It is hoped that the implications of this research can become a basis for the government and stakeholders to formulate more effective policies in increasing the capacity of the city's economy and making a positive contribution to economic growth at regional and national levels.